iSPRING SUITE: A SMARTPHONE APPLICATION-BASED TEST FOR INDONESIAN LANGUAGE SUBJECTS IN ELEMENTARY SCHOOL - Elinda, Muzanni; Maritasari, Donna Boedi; Ramdan, Ahmad Yasar (STKIP Citra Bakti, 2026)
This research aims to develop a smartphone-based digital test using iSpring Suite software for Indonesian Language lessons in elementary schools. The background of this research is the limited evaluation media used by teachers, which are still predominantly paper-based. The study used a research and development method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The resulting product is an interactive test application designed to facilitate teacher assessment and provide a more engaging learning experience for students. The research was conducted in a fifth-grade class at Wajageseng Elementary School with 37 students. The instruments used included a media expert validation sheet, a material expert validation sheet, and a student response questionnaire. The media expert validation results showed a score of 86.67%, categorized as very appropriate, the material expert validation results scored 72%, and the student response results reached 86.40%, categorized as very good.